The complete mitogenome of ‘Zaohoucheng’, an important Saccharina japonica cultivar in China - Zhang, Jing (Mitochondrial DNA B Resour, 2017)
Saccharina japonica is one of the most important economic seaweeds. Here, complete mitogenome of S. japonica cultivar ‘Zaohoucheng’ were reported. Its circular mapping organization with the length of 37,657 bp had an overall A + T content of 64.70% and encoded three rRNAs, 25 tRNAs, 35 known mitochondrial proteins and three ORFs. From the total alignment of S. japonica and its cultivar ‘Zaohoucheng’, only 12 nucleotide substitutions were detected. Gene arrangement and component of ‘Zaohoucheng’ mitogenome were identical to those of reported Saccharina species, indicating highly conservative evolution. The phylogenetic analysis showed that ‘Zaohoucheng’ had a closer relationship with S. japonica which strongly supported the parental origin of 'Zaohoucheng'.